10.0k views
2 votes
\begin{aligned} &A = 7x^2-3x+10 \\\\ &B = -4x^2+6x-4 \end{aligned} ​ A=7x 2 −3x+10 B=−4x 2 +6x−4 ​ A-B=A−B=A, minus, B, equals Your answer should be a polynomial in standard form.

1 Answer

2 votes

Answer:

A-B = 11x²-9x+14

Explanation:

Given the polynomial functions A = 7x^2-3x+10 and B = -4x^2+6x-4, we are to find the value of A - B.

A-B = 7x²-3x+10 - ( -4x²+6x-4)

open the parenthesis

A-B = 7x²-3x+10 + 4x²-6x+4

collect the like terms

A-B = 7x² + 4x²-3x-6x+10+4

A-B = 11x²-9x+14

Hence the difference between both quadratic equation in standard form is 11x²-9x+14

User Vijay Sahu
by
4.9k points